Eficacia de la dexametasona como terapia complementaria, en meningitis bacteriana aguda por Streptococcus pneumoniae, en adultos - Quintero Villalobos Moreida; Ferrer Ocando Olmedo; Ferrer Ocando Yenny; Vizcaíno María; Gonzáles Liliam (Kasmera, 2006)
Abstract: Acute bacterial meningitis due to S. pneumoniae in adults has a high morbidity rate. Corticosteroids are not used routinely. Here, complementary therapy with dexamethasona was used in 6 patients who received penicillin plus chloramphenicol. The results showed there was clinical improvement. The continuation of this study with more patients is recommended.